The state of cancer care in Russia: breast cancer. Epidemiology and survival of patients. The impact of the SARS-CoV-2-beta-coronavirus epidemic (clinical and population study) - V. M. Merabishvili; V. F. Semiglazov; A. V. Komiakhov; T. Yu. Semiglazova; P. V. Krivorotko; А. M. Belyaev (ABV-press, 2023)
Background. Breast cancer is the main cause of morbidity and mortality of the female population among economically developed countries, including in Russia. Despite the continued increase in morbidity, mortality is decreasing, which is confirmed by a decrease in the index of accuracy (the ratio of the number of deaths to the sick). Calculations of survival at the population level (the most important criterion for evaluating the activities of the oncological service) in Russia are carried out only on the basis of databases of the population cancer registry of the North-Western Federal District. The accumulated 1.5 million primary cases of malignant tumors allowed for the in-depth development of data on rare tumor localities, including breast cancer among the male population.Aim. To study the impact of the coronavirus pandemic on the dynamics of the process of detection, mortality and survival of breast cancer patients in Russia and in the North-Western Federal District of the Russian Federation.Materials and methods. The material of the study is the reference books of the P. Hertzen Moscow Oncology Research Institute - branch of the National Medical Research Radiology Center, Ministry of Health of Russia, and the N.N. Petrov National Medical Research Oncology Center, Ministry of Health of Russia, and the database of the population cancer registry of the North-Western Federal District, clinical materials of the surgical department of breast tumors of theN.N. Petrov National Medical Research Oncology Center. More than 110 thousand primary cases of breast cancer were selected. Data processing was carried out by standard methods of oncology statistics recommended by the International Association of Cancer Registries (Eurocare program).Results. A significant impact of the coronavirus pandemic on the primary registration of breast cancer in Russia from 2019 to 2020 has been established, with some weakening of its impact in the subsequent period. The pandemic has had a significant impact on the quality of primary registration of patients. The value of the index of accuracy has been set back five years, but there is a sign of its improvement in 2021. The positive dynamics of one-year and five-year survival of patients with breast cancer is shown. The quality of registration of patients with breast cancer by detailed localization and histological structures of breast cancer was investigated. A significant decrease in the mortality of patients was noted when studying the patterns of dynamics in annual mortality over three follow-up periods.Conclusion. A steady increase in the incidence of breast cancer among women has been established, and the negative impact of the coronavirus pandemic has been noted. The mortality rate of the Russian population from breast cancer continues to decrease. The localization and histological structure of the incidence of breast cancer in women remains unchanged. The one-year and five-year survival rate of breast cancer patients continues to grow.